Lateralized Difference in Tympanic Membrane Temperature: Emotion and Hemispheric Activity - Propper, Ruth E.; Brunyé, Tad T. (Frontiers in Psychology, 2013)
We review literature examining relationships between tympanic membrane temperature (TMT), affective/motivational orientation, and hemispheric activity. Lateralized differences in TMT might enable real-time monitoring of hemispheric activity in real-world conditions, and could serve as a corroborating marker of mental illnesses associated with specific affective dysregulation. We support the proposal that TMT holds potential for broadly indexing lateralized brain physiology during tasks demanding the processing and representation of emotional and/or motivational states, and for predicting trait-related affective/motivational orientations. The precise nature of the relationship between TMT and brain physiology, however, remains elusive. Indeed the limited extant research has sampled different participant populations and employed largely different procedures and measures, making for seemingly discrepant findings and implications. We propose, however, that many of these discrepancies can be resolved by considering how emotional states map onto motivational systems, and further examining how validated methods for inducing lateralized brain activity might affect TMT.